Priming good parenting : can positive affective priming influence fathers' causal attributions and consequent disciplinary responses for child misbehaviour? : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Palmerston North, New Zealand - Mackie, Kayla Louise (Massey University, 2017)
This thesis combines affective priming with the cognitive processes and behavioural sequences found in parenting decisions, to explore whether a father’s attributions for child misbehaviour and consequent disciplinary responses can be influenced by a priming intervention. Forty eight fathers of children aged between 5 and 12 years were questioned on their opinions regarding the causes of child behaviour, and how they would choose to respond to or discipline such behaviour, before and following a priming intervention consisting of full-colour images of fathers interacting with their children. These primes differed in content in both emotional valence and the fathering roles depicted dependent upon the group to which participants were randomly assigned. These groups were General Positive, General Negative, Evolutionary Positive, and Evolutionary Negative priming images. Results showed that all research groups were successfully primed, as measured by a word completion task, however consistent and expected changes in attributions for child behaviour and disciplinary choices did not occur due to the priming intervention. Proposed reasons for this include unforeseen priming effects obscuring the main effect, additional corrective cognitive factors altering or obscuring the priming effect, or difficulties with the way the cognitive and behavioural changes were measured. Proposed methods for further exploration in future research regarding how to translate a priming effect into meaningful and consistent change are discussed. Priming as an adjunctive parenting intervention remains an interesting and worthwhile consideration, and ideas around utilisation of this technique are discussed in light of the results of this research.
Keywords: Discipline of children; Parenting; Psychological aspects; Priming (Psychology); Fathers; Psychology; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology